Comparison of Ile-de-France and Merino Precoce Breeds as Pure Breeds and in Crossbreeding with the Boujaâd Breed in Morocco - I. Boujenane (Revue d’Elevage et de Médecine Vétérinaire des Pays Tropicaux, 2005)
The study concerned 1145 performances of ewes and 1411 performances of lambs of Ile-de-France (IF), Merino precoce (MP) and Boujaâd (BO) breeds. The data were collected during eight lambing seasons, from 1997-98 to 2004-05 in a private farm. IF and MP ewes were mated to rams of their corresponding breeds, whereas BO ewes were mated to rams of the three breeds. The ewe breed had a significant effect on the litter size and litter weight at birth, but not on the litter size and litter weight at 70 days (d). IF and MP ewes had a litter size and a litter weight at birth higher than the corresponding performance average of BO ewes. The differences were 0.25 and 0.30 lamb, and 1.45 and 1.22 kg, respectively. Moreover, the mating ram breed did not have a significant effect on the litter size at birth of BO ewes, but it had a significant effect on the litter weight at birth. The performance of ewes crossed with IF and MP rams was on average 0.48 kg higher than that of ewes mated with BO rams. In addition, the lamb genetic group had a significant effect on the lamb weight and viability at 70 d. IF and MP lambs had the highest birth weights, followed by crossbred lambs. However, the weights at 30 and 70 d of the latter were higher than those of the parental breeds. IF lambs’ viability was 6% lower than that of MP and BO lambs, and 11% lower than that of crossbred lambs. The heterosis effect was positive and high for weights at 30 and 70 d, and for survival at 70 d, but negative for birth weights.